Pelanggaran Dalam Hukum Humaniter Internasional Pada Perang Israel Terhadap Palestina - Muslimma, Liska; Widyastuti, Maya; Husna, Lenny (Prosiding, 2024)
International humanitarian law stipulates that parties to conflict must not use weapons and methods that violate this law during war. The prolonged conflict between Israel and the Palestinians has led to various violations of international humanitarian law. These violations include excessive use of military force against civilians, attacks on civilian infrastructure and sieges that cause disproportionate human suffering. The study aims to examine violations of international humanitarian law and the protection of civilians in armed conflict. The research method used was a literature review, with the main source of peer-reviewed journals in the last 10 years. These findings indicate that Israel has violated the principles of international humanitarian law in its attack on Palestine, the principle of separation between military and civilian targets. The attacks on civilians, hospitals, and other civilian facilities indicate violations of humanitarian law. In addition, the study also highlights the role of international organizations and non-governmental agencies in defending civil rights and documenting violations. The study emphasizes the importance of the protection of civilians and the enforcement of humanitarian law in situations of armed conflict. By examining the various case studies and reports available, the study aims to provide policy recommendations to improve compliance with international humanitarian law and strengthen protection mechanisms for civilians in conflict areas. This research is expected to contribute to a better understanding of the legal implications of the Israeli-Palestinian conflict and offer practical solutions to alleviate human suffering in the future.